The Relationship of Physical Activity Intensity And Sleep Quality With The Performance of Pre-Elderly Employees (Study AT PT Bukaka Teknik Utama Tbk) - Azka Qanit Naufan Zakaria; Bazzar Ari Mighra; Kuswahyudi Kuswahyudi; Yasep Setiakarnawijaya; Heni Widyaningsih (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research was conducted to determine the relationship between physical activity intensity and sleep quality on performance of pre-elderly employees of PT Buakaka Teknik Utama Tbk. This research use a quantitative research method with correlative associative study. The participants in this research were pre-elderly employees worked at PT Buakaka Teknik Uta,a Tbk with total 50 respondents with the age range of respondents between 45 to 59 years old. This research use questionnaire or survey distributed to respondents to collect the data. In data analysis, this research using data analysis techniques in the form of multiple regression test with STATA MP 14.2. The results showed that the intensity of physical activity has a significant affect towards employee performance while the quality of sleep not have a significant affect to employee performance. So it is concluded that the longer intensity of physical activity carried out by employees will improve employee performance while employees quality of sleep has no influence significantly on employee performance.